2015
DOI: 10.3177/jnsv.61.154
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regulation of FGF19 and FGF21 Expression by Cellular and Nutritional Stress

Abstract: Summary Fibroblast growth factor 19 (FGF19) and FGF21 are members of a subfamily of the FGFs called endocrine FGFs. FGF19 regulates the bile acid synthetic pathway. FGF19 expression is induced by farnesoid X receptor (FXR), a nuclear hormone receptor activated by bile acids in the small intestine. FGF21 plays an important role in lipolysis that occurs in white adipose tissue. FGF21 expression is stimulated by the nuclear fatty acid receptor peroxisome proliferator-activated receptor a (PPARa) in the liver. FGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
2
17
3
Order By: Relevance
“…Our findings are in agreement with some reports on lack of liver FGF21 changes with calorie restriction in mice and a reduction in circulating FGF21 with energy restriction in humans . Prior evidence from intestinal‐derived cell lines implicates the existence of amino acid sensing mechanisms in the intestine; whether similar sensing mechanisms occur in vivo remains largely unknown. Here, we uncovered that protein restriction upregulated the transcripts for key intermediaries of amino acid sensing and signaling such as Eif2ak4 (GCN2), Eif2ak3 (PERK), Eif2s1 (eIF2α), Atf2 , Atf4 , Ddit3 (CHOP), and Eif4ebp1 (4EBP1) particularly in the duodenum, with marginal changes in the ileum.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in agreement with some reports on lack of liver FGF21 changes with calorie restriction in mice and a reduction in circulating FGF21 with energy restriction in humans . Prior evidence from intestinal‐derived cell lines implicates the existence of amino acid sensing mechanisms in the intestine; whether similar sensing mechanisms occur in vivo remains largely unknown. Here, we uncovered that protein restriction upregulated the transcripts for key intermediaries of amino acid sensing and signaling such as Eif2ak4 (GCN2), Eif2ak3 (PERK), Eif2s1 (eIF2α), Atf2 , Atf4 , Ddit3 (CHOP), and Eif4ebp1 (4EBP1) particularly in the duodenum, with marginal changes in the ileum.…”
Section: Discussionsupporting
confidence: 92%
“…In vitro, mouse colonic epithelial cells which are pre-treated with FGF19 are protected against ROS (H 2 O 2 ) [117]. Conversely, oxidative stress induces FGF19 mRNA expression in vitro, but not in vivo [118]. Furthermore, also in vitro, the activated FGFR4 by FGF19 inhibits Nf-κB signaling [119].…”
Section: Farnesoid X Receptor and Fibroblast Growth Factor 19mentioning
confidence: 99%
“…1,2) It has been reported that FGF21 ameliorates hepatic steatosis and improves insulin resistance of diabetic mice, making it an attractive drug target of metabolic diseases. 3,4) The expression of FGF21 gene is recently reported to be regulated by endoplasmic reticulum (ER) stress, [5][6][7][8] oxidative stress, 5,9) and amino acid deprivation [9][10][11] through activating transcription factor 4 (ATF4). ER stress is caused by overloading misfolded proteins in ER, and it activates three membrane proteins, activating transcriptional factor 6 (ATF6), inositol requiring 1, and PKR-like endoplasmic reticulum kinase (PERK).…”
Section: Abstract: Activating Transcription Factor 4 (Atf4);mentioning
confidence: 99%